The Effects of Transcutaneous Spinal Direct Current Stimulation on Neuropathic Pain in Multiple Sclerosis: Clinical and Neurophysiological Assessment - Berra, Eliana; Bergamaschi, Roberto; De Icco, Roberto; Dagna, Carlotta; Perrotta, Armando; Rovaris, Marco; Grasso, Maria Grazia; Anastasio, Maria G.; Pinardi, Giovanna; Martello, Federico; Tamburin, Stefano; Sandrini, Giorgio; et al. (Frontiers in Human Neuroscience, 2019)
Background. Central neuropathic pain represents one of the most common symptoms in multiple sclerosis (MS) and it seriously affects quality of life. Spinal mechanisms may contribute to the pathogenesis of neuropathic pain in MS. Converging evidence from animal models and neurophysiological and clinical studies in humans suggests a potential effect of transcranial direct current stimulation (tc-DCS) on neuropathic pain. Spinal application of DCS, i.e., transcutaneous spinal DCS (ts-DCS), may modulate nociception through inhibition of spinal reflexes. Therefore, ts-DCS could represents an effective, safe and well-tolerated treatment for neuropathic pain in MS, a largely unexplored topic. This study is a pilot randomized double-blind sham-controlled trial to evaluate the efficacy of ts-DCS on central neuropathic pain in MS patients. Methods. Thirty-three MS patients with central neuropathic pain were enrolled and randomly assigned to two groups in a double-blind sham-controlled design: anodal ts-DCS group (n = 19, 10 daily 20-min sessions, 2 mA) or sham ts-DCS group (n = 14, 10 daily 20-min sessions, 0 mA). The following clinical outcomes were evaluated before ts-DCS treatment (T0), after 10 days of treatment (T1) and one month after the end of treatment (T2): Neuropathic Pain Symptoms Inventory (NPSI), Ashworth Scale for spasticity (AS) and Fatigue Severity Scale (FSS). A subgroup of patients treated with anodal ts-DCS (n = 12) and sham ts-DCS (n = 11) also underwent a parallel neurophysiological study of the nociceptive withdrawal reflex (NWR) and the NWR temporal summation threshold, two objective markers of pain processing at spinal level. Results. Anodal ts-DCS group showed a significant improvement in NPSI at T1, which persisted at T2, while we did not detect any significant change in AS and FSS. Sham ts-DCS group did not show any significant change in clinical scales. We observed a non-significant trend towards an inhibition of NWR responses in the anodal ts-DCS group at T1 and T2 when compared to baseline. Conclusions. Anodal ts-DCS seems to have an early and persisting (i.e., one month after treatment) clinical efficacy on central neuropathic pain in MS patients, probably through modulation of spinal nociception.